Characterization of preconceptional reproductive risk in women of childbearing age - Cala, Liany Jorge; Alonso Castro, Damilex; Avila Barrios, Yusladi; Reyes Frontela, Yanisel; Rodríguez Corrales, Idania (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: The purpose of maternal and child health is to achieve the optimal state for mothers and children, for this, the management of preconceptional reproductive risk constitutes a basic pillar. Objective: To characterize the preconceptional reproductive risk in women of childbearing age in the medical office 19, Policlínico Universitario Juan Bruno Zayas, Mantua municipality in the period from September 2022 to March 2023. Method: An observational, descriptive and transversal study was carried out; the universe was constituted by 358 women of fertile age between 15 and 49 years old, a sample of 186 was selected by non-probabilistic sampling. Theoretical and empirical methods were used, based on an elaborated survey and individual clinical histories, and descriptive statistics were used in absolute and relative frequencies. Results: there was a predominance of the age group between 40 and 49 years with 39.3%, a schooling level of medium technical with 33.3%; as obstetric antecedents, induced abortions, pregnancy-induced hypertension; 25% suffered from arterial hypertension and 21.4% from bronchial asthma, as chronic non-transmissible diseases; 67% of the women were controlled and protected with contraceptive methods; those under 20 years of age were not controlled. Conclusions: it is concluded that preconceptional reproductive risk in women of childbearing age is a problem that requires attention, mainly in women under 20 years of age because they are not under control and women over 40 years of age because they have associated diseases, which contributes to an increase in the rate of infant and perinatal morbidity and mortality.